2015
DOI: 10.5539/jfr.v4n6p28
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Common Seaweeds from the Kenya Coast

Abstract: The gross nutritional profile of 34 seaweed species from three sites (Mkomani, Kibuyuni and Mtwapa) in coastal Kenya were studied. The crude fat, crude protein, crude fibre and crude ash were determined by the standard AOAC methods while the nitrogen-free extract (NFE) was calculated by weight difference of the chemical components. The chemical constituents of the seaweeds varied significantly among the algal divisions, species, months and sites (<em>p</em>&lt;0.05). The major chemical componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
8
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
4
19
8
4
Order By: Relevance
“…The results indicated that seaweed varieties of Hypnea musciformis and Sargassum oligocystum had the highest levels of NFE at 73.07 and 71.42 % respectively. The NFE values for Hypnea musciformis were considerably higher than those reported by Siddique, (2013) and Mwalugha et al, (2015), who obtained 20.60% and 43.76% respectively. In addition, the NFE values for Sargassum oligocystum was higher than 53.21% reported by Azad and Xiang, (2012) and 30.30% reported by Kumar et al,(2011).…”
Section: Proximate Compositioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The results indicated that seaweed varieties of Hypnea musciformis and Sargassum oligocystum had the highest levels of NFE at 73.07 and 71.42 % respectively. The NFE values for Hypnea musciformis were considerably higher than those reported by Siddique, (2013) and Mwalugha et al, (2015), who obtained 20.60% and 43.76% respectively. In addition, the NFE values for Sargassum oligocystum was higher than 53.21% reported by Azad and Xiang, (2012) and 30.30% reported by Kumar et al,(2011).…”
Section: Proximate Compositioncontrasting
confidence: 68%
“…Eucheuma denticulatum and Laurencia intermedia had the highest ash content which differed with (36.21%) and (30.32%) obtained by Mwalugha et al, (2015). Similarly, the ash content of Hypnea musciformis differed with (21.57%) reported by Siddique, (2013) and (20.77%) reported by Mwalugha et al, (2015). In this study the ash content of Sargassum oligocystum was considerably lower than 24.88% reported by Azad and Xiang, (2012) and (42.40%) in Sargassum polycystum obtained by Matanjun et al, (2009).…”
Section: Proximate Compositioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Kadar abu P. tetrastromatica 41,24% (Mwalugha et al 2015) dan T.decurrens 15,64% (Sari 2015). Kadar abu yang tinggi pada rumput laut dapat dipengaruhi oleh adanya garam dan mineral lain yang menempel misalnya Na, Ca, K dan Mg (Yuniarti et al 2013;Yulius et al 2016), semakin banyak kandungan mineral, maka kadar abu semakin tinggi (Nasruddin et al 2016).…”
Section: Komposisi Kimiaunclassified